Liquidity, risks and speed in payment and settlement systems: a simulation approach - Harry Leinonen (Bank of Finland, 2005)
This publication consists of eleven separate studies on payment and settlement systems conducted using simulation techniques. Most have been carried out using the payment and settlement system simulators BoF-PSS1 or BoF-PSS2 provided by the Bank of Finland and presented at the simulator seminars arranged by the Bank. The main focus in the analyses is on liquidity requirements, settlement speed, gridlock situations, gridlock resolving methods, liquidity economising, systemic risk, and the impact of shocks on system performance. The studies look at systems in several countries and cover both RTGS and netting systems as well as securities settlement systems.
URN:NBN:fi:bof-201408071701
Keywords: 330